KONFLIK BATIN TOKOH NOVEL SENJA DAN PAGI KARYA ALFFY REV DAN LINKA ANGELIA: PSIKOLOGI SASTRA - Dwi Tindika; Sri Muryati; Pardyatmoko Pardyatmoko (Universitas Negeri Makassar, 2023)
This study aims to describe the characterizations and inner conflicts experienced by the character Alffy. This research method is descriptive qualitative. The research data is in the form of sentences and quotes that contain characterizations and inner conflicts. The data source for this research is the novel Senja Dan Pagi by Alffy Rev and Linka Angelia. Data collection techniques are reading, recording, and analyzing. The analysis techniques of this research are reduction, data presentation, and conclusions. The results of this study are the characterizations of Alffy's character including responsibility, compassionate, kind, and brave. Inner conflict based on Abraham Maslow's theory that found data on the non-fulfillment of five needs, namely physiological, security, belonging and love, appreciation, and self-actualization. Alffy's character experiences an inner conflict due to unfulfilled needs which causes Alffy's character to feel afraid, sad, disappointed, and hopeless.